Association of circulating leukocyte telomere length with survival in patients with colorectal cancer. Issue 4 (May 2022) - Pauleck, Svenja; Gigic, Biljana; Cawthon, Richard M.; Ose, Jennifer; Peoples, Anita R.; Warby, Christy A.; Sinnott, Jennifer A.; Lin, Tengda; Boehm, Juergen; Schrotz-King, Petra; Li, Christopher I.; Shibata, David; et al.
Abstract: Introduction: Telomere shortening, as seen with aging, can cause chromosomal instability and promote cancer progression. We investigated the association between circulating telomere length and overall and disease-free survival in a sub-cohort of patients with colorectal cancer. Methods: Baseline genomic DNA from blood leukocytes was extracted from N = 92 newly diagnosed stage I-IV patients with colorectal cancer enrolled at the ColoCare Study site in Heidelberg, Germany. Detailed information on clinicodemographic (including age) and lifestyle risk factors, and clinical outcomes (including recurrence and survival) was collected. Telomere length was measured in DNA using multiplex quantitative polymerase chain reaction. Kaplan Meier survival curves were generated comparing shorter to longer telomere lengths with log-rank testing. Results: The mean T/S ratio for study patients was 0.5 (range: 0.3–0.9). Shorter telomeres were associated with older age at baseline. Patients with shorter telomeres experienced a worse overall and disease-free survival, although this association did not reach statistical significance. Kaplan-Meier survival curves for those with circulating telomere length below vs. above the median showed poorer overall (log-rank p = 0.31) and disease-free survival (long-rank p = 0.23). Conclusions: Our results suggest that individuals with shorter telomeres, as seen with aging, may experience a worse overall and disease-free survival after colorectal cancer diagnosis. Larger sample sizes with longer follow-up are needed to further evaluate telomere length as a prognostic biomarker in colorectal cancer progression.